Rheological behavior of biodegradable N -succinyl chitosan- g -poly (acrylic acid) hydrogels and their applications as drug carrier and in vitro theophylline release - Bashir, Shahid; Teo, Yin Yin; Ramesh, Subramaniam; Ramesh, Kasi; Mushtaq, Muhammad Waheed (Elsevier, 2018)
Novel pH sensitive N-succinyl chitosan-g-poly (acrylic acid) hydrogels were synthesized through free radical mechanism. Rheometer was used to observe the mechanical strength of the hydrogels. In vitro degradation was conducted in SIF (pH 7.4). The effect of concentration of monomers, initiator, and crosslinking agent and pH and ionic strength of NaCl, CaCl2, and AlCl3 on swelling of the hydrogels was observed. The results showed that equilibrium swelling ratio was highly influenced by concentration of monomers, initiator, and crosslinking agent concentration, and pH and salt solutions of NaCl, CaCl2, and AlCl3. The swelling kinetics revealed that swelling followed non-Fickian anomalous transport. Furthermore, theophylline loading (DL %) and encapsulation efficiency (EE %) of the hydrogels was in the range of 15.5 ± 0.15–22.8 ± 0.06% and 62 ± 0.15–91 ± 0.26%, respectively. The release of theophylline in physiological mediums was strongly influenced by the pH. The theophylline release was in the range of 51 ± 0.20–92 ± 0.12% in SIF and 7.4 ± 0.02–14.9 ± 0.03% in SGF (pH 1.2), respectively. The release data fitted well to Korsmeyer-Peppas model. The chemical activity of the theophylline suggested that drug maintained its chemical activity after release in vitro. The results suggest that synthesized hydrogels are excellent drug carriers.